2018
DOI: 10.1096/fj.201800969r
|View full text |Cite
|
Sign up to set email alerts
|

Socioenvironmental stressors encountered during spaceflight partially affect the murine TCR‐β repertoire and increase its self‐reactivity

Abstract: Spaceflights are known to affect the immune system. In a previous study, we demonstrated that hypergravity exposure during murine development modified 85% of the T-cell receptor (TCR)-β repertoire. In this study, we investigated whether socioenvironmental stressors encountered during space missions affect T lymphopoiesis and the TCR-β repertoire. To address this question, pregnant mice were subjected throughout gestation to chronic unpredictable mild stressors (CUMS), a model used to mimic socioenvironmental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…We first analyzed the length of these regions and noted that this parameter is not impacted by spaceflight or during the recovery period (Figure 6A). The average length of IgM CDR3 was 15.7 amino acids (AA) in controls and cosmonauts, a value very close to the one (15.5 AA) determined in previous studies of IgM in healthy subjects 32,33 . Then, we wondered whether CDR3 amino acid composition could be affected.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…We first analyzed the length of these regions and noted that this parameter is not impacted by spaceflight or during the recovery period (Figure 6A). The average length of IgM CDR3 was 15.7 amino acids (AA) in controls and cosmonauts, a value very close to the one (15.5 AA) determined in previous studies of IgM in healthy subjects 32,33 . Then, we wondered whether CDR3 amino acid composition could be affected.…”
Section: Resultssupporting
confidence: 57%
“…Dispersion indexes were used to determine whether differences in the repertoire of VDJ associations, or other criteria, exist between groups or time points. 32 The following formula shows, for example, how these indexes (comprised between 0 and 1), were calculated for VDJ associations. These dispersion indexes take into account all associations whatever their frequencies of expression.…”
Section: Calculation Of Dispersion Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by higher serum corticosterone concentrations noticed in mice exposed to 3G during 21 days [41], as well as during the rst two weeks of exposition to the chronic mild stress model (CMS) which is more intense than CUMS because of water and food deprivation periods [42]. So, as previously reported for the TCRβ repertoire [43,44], socio-environmental stressors seem to have less impact on intestinal microbiota than gravity changes.…”
Section: Discussionsupporting
confidence: 59%
“…This model involves the chronic exposure of mice to unpredictable socio-environmental stresses of various types (e.g., confinement, isolation, cage tilt, paired housing, perturbed circadian rhythm) and moderate intensity. It was demonstrated that this type of stressors only modifies 25% of the TCR repertoire [35]. Consequently, it appears that a change in the gravitational force has a much greater impact than socio-environmental stresses on the T-cell antigen receptor repertoire.…”
Section: Effects On the Maturation Of Immune Cellsmentioning
confidence: 99%